Study of the Response of a Three-Dimensional Coupled !ce-Ocean Model to Daily Varying Atmosphenc Forcing. - Riedlinger, Shelley K.; Preller, Ruth H. (1994)
The Naval Research Laboratory developed a coupled ice-ocean model that simulates ice-ocean interactions in response to atmospheric forcing. This model couples the U.S. Navy's Polar Ice Prediction System ice model, which is based on the Hibler ice model, to a diagnostic version of the Bryan-Cox three-dimensional ocean circulation model. A 6-yr simulation was performed using daily atmospheric data from the Fleet Numerical Meteorology and Oceanography Center's Naval Operational Global Atmospheric Prediction System (NOGAPS) for the years 1986 through 1991. Interannual variability in most NOGAPS fields was large. Ice thickness and ice concentration changes responded directly to fluctuations in surface forcing fields. The thinnest ice of the simulation occurred in 1989, 1990, and 1991. In 1990 and 1991, the surface air temperatures were warm compared to the other years, but in 1989 the net longwave radiation from NOGAPS was anomalously large in the summer. In the summer, solar and sensible heat fluxes are the strongest forcing fields, and they add heat into the ice-ocean system causing ice to melt. In the fall, solar heating diminished and the combination of sensible plus latent fluxes, along with longwave radiation, caused a dramatic cooling that resulted in ice growth. In the winter, the sensible heat flux added heat into the system, but the combination of latent heat flux and longwave cooling dominated; the result was further ice growth. Winds have a pronounced effect on ice growth/melt by directly altering the sensible and latent heat fluxes and by indirectly affecting all heat fluxes by altering the distiibution of ice cover and open water. Ice advection may account for more than half of the change in ice thickness in any given month when the winds are strong.